Assessing the Impact of State Human Trafficking Legislation on Criminal Justice System Outcomes. (29th April 2019) - Farrell, Amy; Bouché, Vanessa; Wolfe, Dana
Abstract : Since 2003, state legislatures in the United States have been active in passing legislation aimed at combating human trafficking. To date, all states have passed laws that criminalize acts of human trafficking, though with significant variation in the penalty structure and associated legal provisions. This article examines what aspects of state human trafficking laws are most impactful at increasing the arrest and prosecution of human trafficking suspects. Using panel data on state laws and associated enforcement actions from 2003 to 2012, this study confirms that more comprehensive state laws that invest in antitrafficking resources are most strongly associated with human trafficking arrests and prosecutions. States that make legislative provisions for victim assistance, law enforcement training, statutory task forces, and mandatory reporting have higher antitrafficking criminal enforcement. The political environment in which state human trafficking laws are enacted also influences their enforcement.